2013
DOI: 10.1074/jbc.m112.413153
|View full text |Cite
|
Sign up to set email alerts
|

Domain 1 of Mucosal Addressin Cell Adhesion Molecule Has an I1-set Fold and a Flexible Integrin-binding Loop

Abstract: Background: MAdCAM/␣ 4 ␤ 7 interaction directs lymphocyte homing to mucosal tissues. Results: Four crystal structures demonstrate large differences in the integrin-binding loop and whether a CЈ or D strand is present in D1. Conclusion: The integrin-binding loop of MAdCAM is inherently flexible.Significance: This may reflect a specialization of MAdCAM to mediate rolling and firm adhesion by binding to different ␣ 4 ␤ 7 integrin conformations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…The most ideal target(s) are cell membrane-bound proteins. Although Madcam1 was reported to bind integrin α4β7 and mediate lymphocyte adhesion to vascular surfaces [ 35 ], no direct evidence has indicated that Madcam1 is localized to the membrane. In HCC cells, we found that Madcam1 was primarily located in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…The most ideal target(s) are cell membrane-bound proteins. Although Madcam1 was reported to bind integrin α4β7 and mediate lymphocyte adhesion to vascular surfaces [ 35 ], no direct evidence has indicated that Madcam1 is localized to the membrane. In HCC cells, we found that Madcam1 was primarily located in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Data were reduced in HKL-2000 55 . The DH727.2-ZAM18 peptide structure was phased by molecular replacement in PHENIX 56 using as the search model the Fab fragment of an antibody to Madcam-1 Dld2 as selected by high sequence identity 57 . Likewise, the DH753-ZAM18 structure was phased using a composite search model generated from the Fab fragment of the HIV antibody 10E8 germline heavy chain 58 with the HIV antibody DH501 light chain 24 .…”
Section: Methodsmentioning
confidence: 99%
“…These two loops are responsible for the interaction between MAdCAM-1 and α4β7 ( Sun et al, 2011 ). Furthermore, a shift in D1 topology from the I2-set to I1-set was demonstrated by new crystals of MAdCAM-1 and two different Fabs, inducing a switch of integrin-binding loop from CC’ to CD ( Yu et al, 2013 ). The different conformations seen in crystal structures suggest that the integrin-binding loop of MAdCAM-1 is inherently flexible, which may explain why MAdCAM-1 could mediate both rolling and firm adhesion by binding to integrin α4β7 in different conformational states.…”
Section: Discussionmentioning
confidence: 96%